واقع رقمنة القطاعات العموميه في الجزائر: وزارة التعليم العالي نموذجا - غربي، عادل; حاقة، الأزهاري; خضير، ليلى (University Of Eloued جامعة الوادي, 2024)
إن إستخدام تكنولوجيا الاعلام والاتصال في القطاع العمومي، أصبح ضرورة حتمية نظرا للمزايا الكبيرة التي يتمتع بها ولهذا تسابقت الدول من أجل إستغلالها وإستخدامها، للانتقال من الإدارة التقليدية إلى الإدارة الإلكترونية، ومواكبة التطورات العالمية المتسارعة، لا سيما في تسيير المرافق العمومية، هدفت هده الدراسة إلى معرفة واقع رقمنة قطاع التعليم العالي والبحث العلمي، من خلال التعرف على درجة تبني لتكنولوجيا المعلومات والاتصال، وأهم الإجراءات والتدابير المتخذة من قبل الوزارة الوصية في سبيل تحقيق ذلك، إضافة إلى المشكلات والتحديات التي تواجه رقمنة هذا القطاع. تبين لنا من خلال هذه الدراسة أن اعتماد الرقمنة في قطاع التعليم العالي في الجزائر نتج عنه إعادة النظر في الكثير من السياسيات والممارسات التي كانت سائدة في ظل الإدارة التقليدية، لاسيما من خلال مختلف المبادرات والتدابير التي شرعت فيها الوزارة الوصية مؤخرا بهدف تحقيق شعار صفر ورقة في الجامعة الجزائرية، ورغم ذلك تبقى هناك بعض المعوقات التي تعرقل التحول الرقمي في قطاع التعليم العالي والتي ينبغي أن يتم تداركها في المستقبل Abstract: The use of media and communication technology in the public sector has become an inevitable necessity due to the significant advantages it offers. As a result, countries have competed to exploit and utilize it to transition from traditional administration to electronic administration and keep pace with rapid global developments, particularly in managing public services. This study aimed to assess the state of digitization in the higher education and scientific research sector by examining the extent of the adoption of information and communication technology and the key measures and policies implemented by the overseeing ministry to achieve this. Additionally, it addressed the problems and challenges facing the digitization of this sector. The study revealed that the adoption of digitization in Algeria's higher education sector has led to a reconsideration of many policies and practices that were prevalent under the traditional administrative system, especially through various initiatives and measures recently launched by the overseeing ministry, aiming to achieve the goal of a paperless university in Algeria. Despite these efforts, some obstacles still hinder the digital transformation of the higher education sector, which should be addressed in the future.
مداخلة
Keywords: رقمنة; إدارة الكترونية; تكنولوجيا; وزارة التعليم العالي; جامعة; Digitization; Electronic Administration; Technology; Ministry of Higher Education; University.